Has the COVID-19 pandemic changed attitudes and behaviors concerning cosmetic care and procedures among patients presenting to the dermatology outpatient clinic? A multicenter study with 1437 participants - Aslan Kayıran, Melek; Kara Polat, Asude; Alyamaç, Gökçen; Demirseren, Duriye Deniz; Taş, Betül; Kalkan, Göknur; Özkök Akbulut, Tuğba; Kaya Özden, Hatice; Koska, Mahmut Can; Emre, Selma; Kaya Erdoğan, Hilal; Tükenmez Demirci, Gülşen; et al. (Wiley, 2021)
Background The rate of cosmetic procedures and use of skincare products is considered to be affected during the pandemic period; however, this has not been investigated yet. Objective To determine whether the ongoing pandemic has changed people's habits related to skincare products and cosmetic procedures. Methods We conducted a multicenter survey study covering both private and public hospitals. Sociodemographic characteristics and clinical diagnoses of the patients were noted by dermatologists. A survey was used to determine the type and application areas of skincare products and cosmetic procedures before and during the pandemic, whether the patients were concerned about being infected, and any change in the make-up habits of female patients. Results Of the 1437 patients, 86.7% presented to the hospital due to dermatological complaints and 13.3% for cosmetic procedures. The rate of those that did not use skincare products was 0.05% before and 0.06% during the pandemic. Of the participants, 43.2% had undergone cosmetic procedures before and 38.1% during the pandemic. For both periods, the most frequent cosmetic procedure applied was laser epilation, followed by skincare treatment and chemical peeling. While undergoing these procedures, 34.9% of the patients were concerned about contracting coronavirus. Conclusion There was no significant difference in the use of skincare products and cosmetic procedures before and during the pandemic. The majority of the patients continued to undergo these procedures despite their fear of being infected. This shows that during the pandemic period, patients are concerned with their appearance and continue to undergo cosmetic procedures and pay attention to their skincare.
Keywords: Cosmetic Procedures; COVID-19; Pandemic; Skincare Products